Syrian Refugees’ Perceptions About the Representations of Syria and Syrians on Turkish News Media - Engin Dağdeviren (Medya ve Kültür)
Syria has become the biggest refugee producer since a civil war broke out in 2011 and the majority, over three million, of these refugees are hosted in Turkey. This huge number inevitably causes refugees to be included in public and news media agenda daily. In this regard, this paper aims to present the Syrian refugees’ perceptions of the portrayals of Syria and Syrians on Turkish news media through a qualitative study. 22 Syrian immigrants living in Turkey have been interviewed. To make sure that they have been living long enough to comprehend Turkish and follow the media, the samples were chosen among the participants who had been living in Turkey more than three years. The data were collected through semi-structured interviews and qualitative analysis was applied. The findings show that most of the Syrian refugees percept their countries’ and their own image as negative. Participants strictly claim that media show them as people they are actually not. They say that they are often reflected as being troublemakers. Furthermore, they think that the portrayal of them by the media is deliberately created to shape a powerful negative public opinion against Syria and Syrians, and to achieve this; the news, images and stories are carefully selected among the most extremes. They assert this public opinion is best observed through social media and it is disturbing. Most of the participants say they quit using social media and following the mainstream media not to be offended after some point.